Beyond the Gap: Understanding Gender Disparities in Indonesia’s National Science Olympiad Achievements - Falentino, Charlos; Eryawan Presma Yulianrifat; Syayidah Dinurrohmah; Alphero Tanlianto; Nurul Fitriyah Sulaeman; Atin Nuryadin (PT Mattawang Mediatama Solution, 2024)
This research investigates gender disparities in Indonesia's National Science Olympiad (OSN) Achievements. This research uses mix research, quantitative and qualitative. Data for quantitative analysis we get from secondary data, national achievement center website. Qualitative data we get from questionnaire with free response question, and distributed to students, teachers, and special teachers. For quantitative research we use Mann-Whitney U test whereas qualitative research we use content analysis. This research found that males are dominance to females in almost all subjects of National Science Olympiad Achievements significantly. Social stereotypes about boys using more logic and reasoning while females use more emotion, influence female self-perception and performance in understanding math and science. In terms of biology, it also shows that there are concerns of female participants when participating in OSN, they are in the menstrual period. They felt that when they were menstruating, not only did they feel abdominal pain, they also felt unstable emotions. This reduces the performance of female students when participating in the OSN Competition. The stereotype of females taking care of more household tasks or problems, causing less support from parents to female children than that given to male children. The lack of freedom gained by the female students reduces their study time for OSN preparation